Truncated VP3 protein as anti-tumor agent. - Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Lim, Shen Ni (2010)

(untitled)
The present invention discloses proteinaceous apoptin-like containing truncated VP3 genes that can induce apoptosis in tumor cells or transformed cells. The functional truncated fragments having the same kind of activity and specificity as apoptin, possibly in different amounts. The truncated fragments are provided with a tag or fusion protein, and preferably the proteins are non-denatured.